Zwicknia gen. n., a new genus for the Capnia bifrons species group, with descriptions of three new species based on morphology, drumming signals and molecular genetics, and a synopsis of the West Palaearctic and Nearctic genera of Capniidae (Plecoptera) - Murányi, Dávid; Gamboa, Maribet; Orci, Kirill Márk (Zootaxa, 2014)
Zwicknia Murányi, gen. n. is erected for the Capnia bifrons species group sensu Zhiltzova, 2001 with the description of three new species based on morphology, mating call, and the mitochondrial DNA marker cytochrome c oxidase I: Z. acuta Murányi & Orci, sp. n., Z. kovacsi Murányi & Gamboa, sp. n. and Z. rupprechti Murányi, Orci & Gamboa, sp. n.. Zwicknia bifrons (Newman, 1838) comb. n. is selected as the type species and redescribed. The other three species placed into Zwicknia, gen. n., Z. sevanica (Zhiltzova, 1964) comb. n., Z. tuberculata (Zhiltzova, 1964) comb. n., and Z. turkestanica (Kimmins, 1950) comb. n. are redescribed based only on morphological characters. Comparative morphological studies and newly discovered characters of the genitalia has allowed for the first time a synopsis of the adults of the West Palaearctic and Nearctic genera of Capniidae. Arsapnia Banks, 1897 (type species: A. decepta Banks, 1897 comb. rev.) is removed from synonymy with Capnia Pictet, 1841 with new combinations, Arsapnia arapahoe (Nelson & Kondratieff, 1988) comb. n., A. coyote (Nelson & Baumann, 1987) comb. n., A. pileata (Jewett, 1966) comb. n., A. sequoia (Nelson & Baumann, 1987) comb. n., A. teresa (Claassen, 1924) comb. n., A. tumida (Claassen, 1924) comb. n., and A. utahensis (Gaufin & Jewett, 1962) comb. n. A new sensu stricto diagnosis of Capnia is proposed with comments on the taxa retained in Capnia sensu lato.